Analisis aktivitas fisik pada penyandang obesitas menggunakan smartwatch - Akhmad Sobarna; Henry Asmara; Denok Sunarsi; Anwar Sanusi; Suharja Suharja (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
The occurrence of obesity cannot be separated from lifestyle, such as decreased physical activity. Obesity is considered the first signal of the emergence of non-infectious diseases such as diabetes and cholesterol. This study aims to determine physical activity in obese people. Through SmartWatch, people will get data that is footsteps, heart rate, calories. Method: This research using experiment research or Single-Subject Research called SSR. Subjects had 110 kg in weight and 171cm in height with a BMI of 37,6 (Very Fat/Obesity). Analysis of the physical activity of obese people using the active lifestyle rubric and SmartWatch. The research findings that the average score obtained by obese subjects for the footstep category was 1,704 (very low category), which means that the physical activity carried out is also included in the light physical activity category. The average score for the heart rate category obtained by the subject was 67bpm which was included in the normal and low categories, while for the category of calories in and out, the average score obtained was 44 calories used, including into the low category. Physical activity of obese people based on monitoring using SmartWatch also concluded that the active lifestyle of an obese person is very low or low; this can be seen from the results of monitoring physical activity, namely footsteps, heart rate, calories, and Body Mass Index (BMI).